Analisis yuridis pengaturan pengelolaan zakat dan pajak menurut sistem hukum di Indonesia dan Malaysia - Yudi Wicaksono Pratama; Kadek Wiwik Indrayanti (Jurnal Cakrawala Hukum, 2021)
This paper aims to examine the comparison of the regulatory model for zakat and tax management according to the legal system in Indonesia and Malaysia. The research method used is normative legal research using a comparative approach and statute (statute approoach). The results show that the Indonesian and Malaysian governments have a role as facilitators in managing zakat tax. Taxes are collected centrally, and are regulated by law. Meanwhile, the difference between the management of zakat and tax in Indonesia and Malaysia is that it lies in the zakat management institution, zakat regulation in the law, the supervisory agency for zakat management institutions, the zakat fund management and distribution agency, and the zakat fund management program. There are problems in managing zakat in Indonesia, namely zakat management is still carried out in a simple manner, the low level of public trust in amil zakat institutions, the dualism of zakat management institutions, weak application of organizational management principles, low mastery of technology by zakat institutions and low understanding of zakat among the community. So it can be recommended that income zakat can be equated with income tax, namely not as a deduction factor for income tax but as a non-refundable tax credit. there is a need for a supervisory and coordinating regulator and a computerized system.How to cite item: Pratama, Y. W., Indrayanti, K.W. (2020). Analisis yuridis pengaturan pengelolaan zakat dan pajak menurut sistem hukum di Indonesia dan Malaysia. Jurnal Cakrawala Hukum, 12(1). 110-119.doi:10.26905/idjch.v12i1.5724.80.